2020
DOI: 10.1002/ece3.6870
|View full text |Cite
|
Sign up to set email alerts
|

The effect of grazing on winter survival of midday gerbil (Meriones meridianus) of different genders

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 85 publications
0
12
0
Order By: Relevance
“…The activity patterns of Midday gerbil and NTJ in the grazing exclusion area showed high similarity in different seasons, and the separation degree in the temporal niche between two species was low. Studies in the same study area showed that food availability in the grazing exclusion area was significantly higher than that in the grazing area (Yang et al, 2020). Midday gerbils and NTJ have a similar diet, but higher food availability alleviated the pressure of food competition.…”
Section: Coexistence Strategies Of Two Rodent Speciesmentioning
confidence: 92%
See 4 more Smart Citations
“…The activity patterns of Midday gerbil and NTJ in the grazing exclusion area showed high similarity in different seasons, and the separation degree in the temporal niche between two species was low. Studies in the same study area showed that food availability in the grazing exclusion area was significantly higher than that in the grazing area (Yang et al, 2020). Midday gerbils and NTJ have a similar diet, but higher food availability alleviated the pressure of food competition.…”
Section: Coexistence Strategies Of Two Rodent Speciesmentioning
confidence: 92%
“…The vegetation is sparse, and the plants are mainly xerophytic, super xerophytic and halophytic shrubs. Midday gerbil, NTJ, desert hamsters (Phodopus roborovskii) and Mongolian five-toed jerboa (Orientallactaga sibirica) are dominant small-mammal species (Yang et al, 2020). Other natural enemies include Eurasian eagle owl (Bubo bubo), Marbled polecat (Vormela peregusna), and Corsac fox (Vulpes corsac; Yuan et al, 2018).…”
Section: Study Areamentioning
confidence: 99%
See 3 more Smart Citations